CSR Strategy Creation - Matkó, Andrea (International Journal of Engineering and Management Sciences, 2018)
The starting point for the need for social responsibility is to combat the deterioration and destruction of social and environmental values. The social and economic factors induce both society and the economy, including companies, to prioritize their social role. Corporate responsibility needs to be incorporated into the company's strategy so that it can be more planned in the long term, since CSR can thus maximize its impact, ultimately leading to maximizing profits. To be able to develop a strategy, we must first look at the broader environment to which we can apply PEST analysis, by analyzing the social, legal, polo-social and social environment. To take a closer look at the company's narrower environment, we can use the SWOT analysis to identify the company's strengths, weaknesses, opportunities and dangers. Based on these, the Hoshin Kanri method can be used to transform the company's own CSR strategy both short and long-term in order to become part of the corporate culture.